Association of Severe Tongue Edema With Prone Positioning in Patients Intubated for COVID‐19. (31st July 2021) - Walsh, Amanda; Peesay, Tejasvi; Newark, Annemarie; Shearer, Sarah; Parsa, Keon; Pierce, Matthew; Gao, William Z.
Abstract : Objectives/Hypothesis: Prone positioning is frequently used in patients intubated for COVID‐19‐related lung injury to improve oxygenation. At our institution, we observed severe tongue edema develop in some of these patients. Hence, we sought to determine the incidence of tongue edema in this cohort and whether prone positioning was a risk factor associated with this complication. Study Design: Retrospective cohort study. Methods: A single‐system retrospective cohort study of patients intubated for respiratory failure secondary to COVID‐19 who subsequently developed clinically notable tongue edema from March 13 to July 5, 2020. Results: 260 patients were intubated for COVID‐19‐related respiratory failure during the study period. 158 patients (60.8%) underwent at least one episode of proning. Twelve patients in total (4.6%) developed clinically significant tongue edema. Eleven of the twelve patients (91.7%) who developed tongue edema underwent proning prior to the development of edema. Prone positioning was associated with an increased incidence of tongue edema (odds ratio [OR] 7.56, 95% confidence interval [CI] 0.96–59.46, P = .027). In all proned patients who developed edema, this complication was noted during proning or shortly after supination (range, 0–4 days). Tongue edema was primarily managed with conservative measures; one patient required tracheostomy for definitive management. Conclusions: Tongue edema appears to develop in a subset of patients with COVID‐19 who are intubated. It appears to be associated with prone positioning but is likely multifactorial in nature. Further investigation into its incidence and pathophysiology is warranted. Level of Evidence: 4 Laryngoscope, 132:287–289, 2022